Loss of Myh14 Increases Susceptibility to Noise-Induced Hearing Loss in CBA/CaJ Mice - Xiaolong Fu; Linqing Zhang; Yecheng Jin; Xiaoyang Sun; Aizhen Zhang; Zongzhuang Wen; Yichen Zhou; Ming Xia; Jiangang Gao (Neural Plasticity)
MYH14 is a member of the myosin family, which has been implicated in many motile processes such as ion-channel gating, organelle translocation, and the cytoskeleton rearrangement. Mutations in MYH14 lead to a DFNA4-type hearing impairment. Further evidence also shows that MYH14 is a candidate noise-induced hearing loss (NIHL) susceptible gene. However, the specific roles of MYH14 in auditory function and NIHL are not fully understood. In the present study, we used CRISPR/Cas9 technology to establish a Myh14 knockout mice line in CBA/CaJ background (now referred to as Myh14−/− mice) and clarify the role of MYH14 in the cochlea and NIHL. We found that Myh14−/− mice did not exhibit significant hearing loss until five months of age. In addition, Myh14−/− mice were more vulnerable to high intensity noise compared to control mice. More significant outer hair cell loss was observed in Myh14−/− mice than in wild type controls after acoustic trauma. Our findings suggest that Myh14 may play a beneficial role in the protection of the cochlea after acoustic overstimulation in CBA/CaJ mice.